Professional identity of students in the context of professionalization - Muradyan, Elena; Manukyan, Mariam (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
The article discusses the problem of the formation of professional identity (PI) among students as the most important criterion for the professionalization of the individual. The necessity of considering the category of “professionalization” from the point of view of a systematic approach is emphasized. It is focused also on the blurring of “substantive boundaries” between such concepts as the professionalization of a person and his professional development. A comprehensive comparative analysis revealed the presence of different approaches of the interpretation of the socio-psychological phenomenon of professional identity. The problems that arise in the process of professionalization of students in connection with the formation of their professional identity in the context of educational and professional activities are revealed. The specificity of the university education is considered. The factors hindering the formation of professional identity in the system of higher education are described. Students’ satisfaction with the quality of education is proposed to be considered as a predictor of the formation of professional identity. However, attention is drawn to the influence of a person’s individual characteristics, to the so-called “internal factors”, which “provide” a certain amount of subjectivity of such a concept as “student satisfaction”. The role of the phenomenon of professional identity in the context of the professionalization of the individual is discussed. The phenomenon of professional identity is considered from the point of view of the “ideological” readiness of a person for a profession. It is proposed a version of the possible content load of the definition of the phenomenon of professional identity. It is necessary to identify external and internal factors to create optimal conditions for the formation of professional identity among students. Attention is drawn to the relationship between the formation of professional identity and personal development.